An Analysis of the Curriculum Ideology in the Lesotho General Certificate of Secondary Education English Language Syllabus - Moea, Kananelo Sylvester (Innovare Journal of Education, 2023)
The role of the English Language is undeniable in maintaining the growth and development of skilled workforces that are globally compatible. This study sets out to analyze the curriculum ideology of the Lesotho General Certificate of Secondary Education (LGCSE) English Language syllabus. The study was qualitatively conducted through the use of document analysis- analyzing the syllabus document. The findings reveal that the LGCSE English Language syllabus has the four curriculum ideologies, though in varying degrees. It appears that the dominant ideology in this syllabus is the learner-centered ideology which appears in four syllabus aims, followed closely by social efficiency appearing in three aims, the social reconstruction appearing in two aims. Trailing behind is the scholar’s academic ideology appearing in one syllabus aim. This LGCSE English Language syllabus positions a learner largely as an affiliate of society and also one who can function effectively in various milieus in a society. The current study suggests curriculum ideology awareness programs should be given to teachers and prospective teachers of the English Language to assist them in their teaching of the English Language. The study also recommends that a survey study can be conducted on teachers and teacher educators before designing the national curriculum of Lesotho because much curriculum is affected by the ideology of the teacher.